Globalization of insecurity? Toughts on the field of the professionals on the management on uncertainties and the analiysis of the trasnationalization of the processes of (in) securitization - Bigo, Didier (Universidad Nacional del Litoral, 2020)
This article suggests a discussion on the premises on which rest a specific vision of global (in)security —as a «natural» consequence of the attacks suffered by the US, Australia, Turkey, Spain, and very recently the United-Kingdom— and the corollary of a unique and efficient solution: the globalisation of security professionals and their cooperation against barbarism. Referring to Pierre Bourdieu and Michel Foucault’s works, the author tries to understand when and how this discourse on the «globalisation of (in)security» developed through the notions of field of the professionals of unease management and of transnationalisation of (in)securisation processes. A particular attention is given to the way in which these processes are linked to the transformations of political violence but also to the European and Transatlantic development of the police, military, and intelligence agencies, to their structuration in a professional field, and to their effects on our societies of risk, doubt, and uncertainty.